Impacts of climate change and environmental degradation on children in Malaysia - Sahani, Mazrura; Othman, Hidayatulfathi; Kwan, Soo Chen; Juneng, Liew; Ibrahim, Mohd Faiz; Hod, Rozita; Zaini, Zul'Izzat Ikhwan; Mustafa, Maizatun; Nnafie, Issmail; Ching, Lai Che; Dambul, Ramzah; Varkkey, Helena; et al. (Frontiers in Public Health, 2022)
The impacts of climate change and degradation are increasingly felt in Malaysia. While everyone is vulnerable to these impacts, the health and well-being of children are disproportionately affected. We carried out a study composed of two major components: The first is comprised of environmental epidemiology research providing evidence of increasing rainfall intensities, air pollution and haze impacts on children hospitalisation and mortality in Malaysia. The second component consists of three community surveys on marginalised children conducted in Pulau Gaya, Sabah, among the indigenous Temiar tribe in Pos Kuala Mu, Perak, and in Kuala Lumpur’s poor urban communities (B40) in PPR Sg. Bonus. The environmental epidemiological research is comprised of three sub-studies: i) a study with a global climate model (GCM) for simulating specific health-sector climate indices; ii) a time-series study to estimate the risk of childhood respiratory disease attributable to ambient air pollution; and iii) a case-crossover study to identify the association between haze and under-five mortality in Malaysia. The community surveys are cross-sectional studies employing a socio-ecological approach using a standardised questionnaire. Our environmental epidemiology studies showed that Malaysia has been experiencing increasing rainfall intensity over the years, leading to increased incidences of other weather-related events. The air quality has worsened, while air pollution and haze have been linked to an increased risk of hospitalisation for respiratory diseases among children. Although no clear association between smoke haze and under-five mortality was found in the case-crossover study, the lag patterns suggested that health effects could be more acute if smoke haze occurred over a longer duration and at a higher intensity. The community surveys revealed how children adapt to climate change and environmental degradation. An integrated model was established that consolidates our overall research processes and demonstrates the crucial interconnections between environmental challenges exacerbated by climate change. A call to the education sector to strengthen the climate-smart environment in school is recommended. The awareness of the impending climate change and its cascading impact on children’s health should be instilled from early school age